ANALISIS KEBUTUHAN IMPLEMENTASI BLENDED LEARNING BERBASIS LMS PADA MAHASISWA CALON GURU - Aldi, Suhardi; Ihsan, Ikhlashul; Afni Yulistiawati, Nur; Fitriah, Nurul; Yusrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
21st-century learning requires higher education institutions to integrate technology into the teaching process, one of which is through blended learning based on a Learning Management System (LMS). This study aims to analyse the needs for the implementation of LMS-based blended learning among prospective teacher students in the Primary School Teacher Education Programme (PGSD) at Lamappapoleonro University. The research was conducted in March 2026 using a descriptive quantitative method with purposive sampling of 53 sixth-semester students. The instrument consisted of a closed-ended questionnaire using a Likert scale with 25 items covering seven aspects: technological readiness, digital literacy, LMS experience, LMS feature requirements, learning model preferences, digital learning barriers, and expectations regarding blended learning. The results indicate that technological readiness and digital literacy fall into the good category, whilst LMS usage experience and the ability to overcome digital barriers remain in the fairly good category. LMS feature requirements and blended learning model preferences range from fairly good to good, whereas students expectations regarding blended learning reach the very good category. The gap between device readiness and digital operational competence indicates the need for a structured LMS orientation programme prior to full implementation.